Cardiac Tolerability of Pertuzumab Plus Trastuzumab Plus Docetaxel in Patients With HER2-Positive Metastatic Breast Cancer in CLEOPATRA: A Randomized, Double-Blind, Placebo-Controlled Phase III Study - Swain, Sandra M. (AlphaMed Press, 2013)
INTRODUCTION. We report cardiac tolerability of pertuzumab plus trastuzumab plus docetaxel versus placebo plus trastuzumab plus docetaxel observed in the phase III study CLEOPATRA in patients with HER2-positive first-line metastatic breast cancer (MBC). PATIENTS AND METHODS. Left ventricular ejection fraction (LVEF) ≥50% and ECOG performance status of 0 or 1 were required for study entry. During the study, LVEF assessments took place every 9 weeks. Pertuzumab/placebo was given at 840 mg, then 420 mg q3w; trastuzumab was administered at 8 mg/kg, then 6 mg/kg q3w, and docetaxel was initiated at 75 mg/m(2) q3w. RESULTS. The incidence of cardiac adverse events (all grades) was 16.4% in the placebo arm and 14.5% in the pertuzumab arm, with left ventricular systolic dysfunction (LVSD, all grades) being the most frequently reported event (8.3% versus 4.4% in the placebo and pertuzumab arm). Declines in LVEF by ≥10% points from baseline and to <50% were reported in 6.6% and 3.8% of patients in the placebo and pertuzumab arm, respectively. Seventy-two percent (placebo arm) and 86.7% (pertuzumab arm) of those patients recovered to a value ≥50%. The incidence of symptomatic LVSD was low, occurring in 1.8% (n = 7) versus 1.0% (n = 4) of patients in the placebo and pertuzumab arm. In 8/11 patients, the symptomatic LVSD had resolved at data cutoff. CONCLUSION. The combination of pertuzumab plus trastuzumab plus docetaxel did not increase the incidence of cardiac adverse events, including LVSD, compared with the control arm in HER2-positive MBC. The majority of cardiac adverse events were reversible.